Feasibility Study of Pavement Repair Using The Benefit-Cost Ratio Method on The Jember District Boundary To Lumajang City Boundary Road Section - Rendy Zesario Akbar; Budi Witjaksana; Jaka Purnama (International Journal Labs, 2025)
Road damage frequently occurs due to poor construction quality, excessive vehicle loads, and extreme weather conditions. The Lumajang City Limit - Jember District Limit road segment has experienced significant damage at several points, primarily caused by vehicles carrying loads exceeding the designated capacity. This research aims to evaluate the current condition of the road, estimate the repair costs, and analyze the economic feasibility of the proposed repair works. The study employs a comprehensive methodology involving field surveys to collect primary data, such as the extent and types of road damage, and secondary data, including traffic volume and vehicle loading. The repair cost is calculated using the overlay method, which accounts for the required structural enhancements to improve road performance. The findings reveal that the total repair cost is estimated at IDR 227,301,086,503. Additionally, the economic feasibility analysis yields a Benefit-Cost Ratio (BCR) of 12.53, indicating that the repair project is highly viable from an economic perspective. These results provide a solid basis for prioritizing repair works and ensuring that investments in road infrastructure deliver significant economic benefits.